Field notes contributed by Dick Bierman, Cherokee, Iowa, winter 1983-1984 - Bierman, Dicket al (1983)
Field notes were contributed by Dick Bierman, Cherokee, Iowa, winter 1983-1984. Northern Harriers were seen and noted in red as very unusual in the area at that time of year. A Northern Goshawk and Varied Thrush were documented. Thousands of Lapland Longspurs were seen along the road between Cherokee and Sac City in Sac County. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1983-1984. Epson - sheet feed